Propuesta de un proceso de investigación cuantitativa. Aplicación en la caracterización de las mypes productoras de software - Amable Ciudad, Miriam Elizabeth (2015)
This article highlights both the quantitative research process and its implementation to achieve the objective of identifying the level of quality in software producing mypes. The current project is aimed at students in their role as researchers, considering that one of the strategic objectives of the institutions of higher education is to promote the culture of research, look for differences in findings, obtain superior training and to be more competitive. The quantitative research process gives way to the realization of the primary methods in obtaining the characterization of software producing mypes in Lima. This allows one to identify the quality of their software.